MO674SHORT DAILY HOME HEMODIALYSIS PROGRAM, IN NEPHROCARE HEMODIALYSIS CENTER: REPORT STUDY. (29th May 2021) - Hebibi, Hadia; Attaf, David; Ciroldi, Magali; Cornillac, Laure; Chazot, Charles; Canaud, Bernard
Abstract: Background and Aims: Several studies showed that DHHD improved survival and quality of life and allowed a lower cost for health system. The aim of this study was to describe our first experience of DHHD in our dialysis center. Method: We included 9 dialyzed patients trained on Nx Stage® machine (Fresenius Medical Care) from February to December 2020. Data was retrospectively obtained through review of our medical electronic records (Euclid®). Results: Among 9 patients trained, 8 were installed at home, with an average follow up of 7 months. 6 patients were dialyzed in self hemodialysis facilities. The mean age was 45 years (28-71), 6 women, BMI: 24 kg/m2 (21-30), dialysis vintage: 5 years and 7 patients are on transplant list. The Charlson score was: 5 (4-8), 5 patients had a residual diuresis> 500 ml/d. The average training duration was 5 weeks (4-8). Our training program targeted the self-puncture of AVF and the self-assembly of the machine by the patient. 100% of AVF were cannulated through Buttonhole technique. 6 patients were dialyzed 6 times a week and only one patient needed anticoagulants. The blood pressure improved on the first days of DHHD (↓ 50% of drugs for 50% of patients). Hemoglobin level maintained between 10-12 g/dl with ↓ EPO. The mineral metabolism status was improved for all patients, with stopping of binders in one case. DHHD reduced symptoms like fatigue, cramping and post-dialysis recovery for all patients, and allowed for patients a better socio-professional integration. A medico-economic analysis is conducted. Conclusion: DHHD improved blood pressure, anemia, mineral status and quality of life. Through economy in medicaltransport and better socio-professional integration DHD provides savings for the health system